GROWTH AND OPENNESS RELATIONSHIP IN THE EU15: PANEL DATA ANALYSIS - Uğurlu, Erginbay (Ekonomika, 2010)
Conventional wisdom suggests that openness of an economy promotes economic growth. There is still argument among economists concerning how a country’s macroeconomic variables and its economic growth interact in numerous econometric studies by using panel data. This paper examines the impact of openness on economic growth for the EU-15 area in 1996–2003. In our empirical work, we have used the panel data technique which is also called longitudinal data or cross-sectional time series data. Panel data is generally concerned with choosing among three alternative regressions that are named fixed effects, random effects and pooled model estimation. The variables used are growth, openness, price level, investment and government share of RGDP. We find that openness has had a weak but negative impact on economic growth in this region over this period. Also, we have found that an increase in investment and a decrease in government expenditure have supported economic growth in the EU-15 countries.